HOW HAS SOUTH AFRICA’S LAND REDISTRIBUTION PROGRAM IMPROVED WOMEN’S LIVELIHOODS? - Qayiso O.; Modiba F.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The issue of access to land has been a dilemma for most women especially those who depend on it for their livelihoods. Often access to land has been denied to this group due to the inequalities that exist in some societies that rendered women inferior to men or lacking rights to own land. Despite the limitations, women have been working and depending on land for centuries as a means to secure their households' livelihoods. In South Africa, some of the post-apartheid policies aimed at affording equal access to land thereby using the land redistribution program to ensure that women farmers can equally access land. Although the land policy has been well researched much attention has not been given to how the redistribution process has influenced women farmers' livelihoods and their sustainability. This paper reviews how the land redistribution program has contributed to the livelihoods and sustainability of women farmers in the Buffalo City Municipality. Explorative qualitative research was conducted to understand the effects of the land redistribution program on the livelihoods of women farmers. The findings of the paper revealed that access to land has contributed to the expansion of livelihoods of women farmers and community members. This was enabled by increased outputs resulting from working from big farms compared to what they could access initially before participating in the land redistribution program. However, the absence of natural, financial, and physical capital proved to affect the sustainability of women's farms as lack of ownership of land threatens future livelihoods.